Uncovering novel bacterial and archaeal diversity: genomic insights from metagenome-assembled genomes in Cuatro Cienegas, Coahuila - Rodríguez-Cruz, Ulises E.; Castelán-Sánchez, Hugo G.; Madrigal-Trejo, David; Eguiarte, Luis E.; Souza, Valeria (Frontiers in Microbiology, 2024)
A comprehensive study was conducted in the Cuatro Ciénegas Basin (CCB) in Coahuila, Mexico, which is known for its diversity of microorganisms and unique physicochemical properties. The study focused on the “Archaean Domes” (AD) site in the CCB, which is characterized by an abundance of hypersaline, non-lithifying microbial mats. In AD, we analyzed the small domes and circular structures using metagenome assembly genomes (MAGs) with the aim of expanding our understanding of the prokaryotic tree of life by uncovering previously unreported lineages, as well as analyzing the diversity of bacteria and archaea in the CCB. A total of 325 MAGs were identified, including 48 Archaea and 277 Bacteria. Remarkably, 22 archaea and 104 bacteria could not be classified even at the genus level, highlighting the remarkable novel diversity of the CCB. Besides, AD site exhibited significant diversity at the phylum level, with Proteobacteria being the most abundant, followed by Desulfobacteria, Spirochaetes, Bacteroidetes, Nanoarchaeota, Halobacteriota, Cyanobacteria, Planctomycetota, Verrucomicrobiota, Actinomycetes and Chloroflexi. In Archaea, the monophyletic groups of MAGs belonged to the Archaeoglobi, Aenigmarchaeota, Candidate Nanoarchaeota, and Halobacteriota. Among Bacteria, monophyletic groups were also identified, including Spirochaetes, Proteobacteria, Planctomycetes, Actinobacteria, Verrucomicrobia, Bacteroidetes, Candidate Bipolaricaulota, Desulfobacteria, and Cyanobacteria. These monophyletic groups were possibly influenced by geographic isolation, as well as the extreme and fluctuating environmental conditions in the pond AD, such as stoichiometric imbalance of C:N:P of 122:42:1, fluctuating pH (5–9.8) and high salinity (5.28% to saturation).